Management of diarrhoea by Siddha Physicians and an indepth study of anti-diarrhoeal drugs used by them - Sivagnanamany, P. (M.Phil. in Siddha Medicine, 1999)
This epidemiological study deals with the management of diarrhoea by 31 siddha by 31 siddha physicians in 4 MOH Divisions of Jaffna District. It also studies indepth the anti-diarrhoeal drugs used by them. A literature study covers all aspects of diarrhoea and discusses concepts of the indigenous system in comparison with the western system. Data were collected using researcher administered questionnaire observation of drug preparation and reading manuscripts on medicines in the possession of the physicians. The physicians use 47 drugs in different forms such as kudineer, chooranum, pill, senthooram, etc. to treat diarrhoeas. These drugs are used either singly or in combinations. Nine are identified as common drugs used by them. Ingredients of the drugs, method of preparation and vehicles for the medicine are presented. Further selective issues in management dealing with diet, dehydration, use of western drugs, Health Education and necessity for lab investigation are discussed. It is hoped that the finding and suggestions in this study would help in the recognition and fuller understanding of the management of diarrhoea by the Siddha Physicians.